Methodology and Tools for Pervasive Application Development. (3rd April 2014) - Tang, Lei; Yu, Zhiwen; Wang, Hanbo; Zhou, Xingshe; Duan, Zongtao
Understanding the user's demands and intentions is essential when developing pervasive applications. It ensures proactive decisions and improves usability. However, due to a lack of conceptual development methodology and supporting tools, it is difficult to orient the designs towards user's needs. To make the developer's task feasible, we present a development environment, called PerDE, which supports a novel design method. Our approach combines the notion of the situation with an application model and provides a domain-specific design language and a set of graphical toolkits covering the development life cycle of a pervasive application. We validate our approach on developing a realistic situation and describe the results from a user study that illustrates the expressiveness and usability of PerDE.